DarkCideS 1.0, a global database for bats in karsts and caves - Tanalgo, Krizler C; Tabora, John Aries G; de Oliveira, Hernani Fernandes Magalhães; Haelewaters, Danny; Beranek, Chad T; Otálora-Ardila, Aída; Bernard, Enrico; Gonçalves, Fernando; Eriksson, Alan; Donnelly, Melissa; González, Joel Monzón; Ramos, Humberto Fernández; et al. (Scientific data, 2022)
Understanding biodiversity patterns as well as drivers of population declines, and range losses provides crucial baselines for monitoring and conservation. However, the information needed to evaluate such trends remains unstandardised and sparsely available for many taxonomic groups and habitats, including the cave-dwelling bats and cave ecosystems. We developed the DarkCideS 1.0 ( https://darkcides.org/ ), a global database of bat caves and species synthesised from publicly available information and datasets. The DarkCideS 1.0 is by far the largest database for cave-dwelling bats, which contains information for geographical location, ecological status, species traits, and parasites and hyperparasites for 679 bat species are known to occur in caves or use caves in part of their life histories. The database currently contains 6746 georeferenced occurrences for 402 cave-dwelling bat species from 2002 cave sites in 46 countries and 12 terrestrial biomes. The database has been developed to be collaborative and open-access, allowing continuous data-sharing among the community of bat researchers and conservation biologists to advance bat research and comparative monitoring and prioritisation for conservation.
Keywords: Animals; ekosystém; Databases, Factual; Ecosystem; biodiverzita; zvířata; databáze faktografické; Chiroptera; Biodiversity